2022
DOI: 10.3389/fendo.2022.1013616
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of thyroid involvement in children and adult Langerhans cell histiocytosis: An underestimated endocrine manifestation

Abstract: BackgroundLangerhans cell histiocytosis (LCH) is a rare disease caused by the clonal expansion of CD1a+/CD207+ LCH cells. The thyroid involvement in LCH has mostly been described in case reports.MethodsWe retrospectively evaluated the clinical characteristics, diagnosis, and treatment of 27 children and adult patients with thyroid LCH in our center between 2010 and 2021.ResultsThe incidence of thyroid LCH was 14.00% (7/50) in children and 10.10% (20/198) in adults, respectively. Among patients with thyroid inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 47 publications
(34 reference statements)
1
0
0
Order By: Relevance
“…In Table 1 , only 64.7% of PTC, 41.2% of LCH, and 29.4% of LCH concurrent with PTC were identified among the 22 cases which underwent preoperative FNAC examination. Li et al reported that the sensitivity of FNAC for the diagnosis of thyroid LCH was 37.5%, which was consistent with our study ( 22 ). Goldstein reported a case in which thyroid FNAC accurately distinguished LCH and PTC and proposed that PTC and LCH cells showed nuclear grooves, LCH cells had more granular cytoplasm, however, PTC showed a large number of cubic/columnar cells forming small papillary structures and produced a small amount of glia ( 6 ).…”
Section: Discussionsupporting
confidence: 93%
“…In Table 1 , only 64.7% of PTC, 41.2% of LCH, and 29.4% of LCH concurrent with PTC were identified among the 22 cases which underwent preoperative FNAC examination. Li et al reported that the sensitivity of FNAC for the diagnosis of thyroid LCH was 37.5%, which was consistent with our study ( 22 ). Goldstein reported a case in which thyroid FNAC accurately distinguished LCH and PTC and proposed that PTC and LCH cells showed nuclear grooves, LCH cells had more granular cytoplasm, however, PTC showed a large number of cubic/columnar cells forming small papillary structures and produced a small amount of glia ( 6 ).…”
Section: Discussionsupporting
confidence: 93%